Comparative biology of mediterranean fruit fly in star fruit and mango - Amaral, Maria Caroline Aguiar (2023)
Ceratitis capitata is a polyphagous species adapted to the most diverse hosts. The life cycle of C. capitata is influenced by the host species in which it develops, and information about its biological data in star fruit is scarce. This study aimed to characterize the biological cycle of C. capitata in star fruit and mango. Portions of 20 g were offered in Petri dishes lined with moistened filter paper to 20 first-instar larvae up to three hours of age. Evaluations were performed daily, quantifying the period and larval survival, pupal viability and mass (puparia weighed at 24 hours of age), longevity, egg-adult period, and fecundity. Larval survival ranged from 89.75% in star fruit to 94.25% in mango. Pupal viability and mass were higher in larvae fed mango. The length of the larval period was not affected by the food substrate. Total and daily fecundities were higher in females from larvae fed mango. Both fruits allowed the complete development of C. capitata, but mango is the most suitable host for its development.